The genetic architecture of sporadic and multiple consecutive miscarriage - Triin Laisk; Ana Luiza G. Soares; Teresa Ferreira; Jodie N. Painter; Jenny C. Censin; Samantha Laber; Jonas Bacelis; Chia-Yen Chen; Maarja Lepamets; Kuang Lin; Siyang Liu; Iona Y. Millwood; et al. (Nature Communications, 2020)
Miscarriage affects around 15% of clinically confirmed pregnancies. Here the authors carry out a large genome-wide association study for sporadic and multiple consecutive miscarriage and suggest links with placental biology.